THE USEFULNESS OF GRAPHIC ORGANIZERS IN ENHANCING READING COMPREHESION ON TEXT TYPES: THE STUDY ON RESEARCH FINDINGS AND ISSUES - Kristina Laora (Jurnal Ilmiah Spectral, 2018)
Reading is one of the skills used to measure the level of academic success. There is a mutual relationship between reading skills and academic success. Students from a variety of backgrounds struggle with reading skill. The purpose of this study was to investigate how graphic organizers can be used in enhancing reading comprehension. Graphic organizers (GOs) facilitate the reading comprehension by providing clear visualizations of ideas and facilitating student reflection. This study constitutes an attempt to elaborate the research evidence regarding the usefulness of GOs on text learning and the various types of graphic organizers, which use different conventions to communicate information and are classified in various ways. It also summarizes research findings and issues on the use of GOs in text types namely narrative, descriptive, recount, procedure and report. The result showed that in using graphic organizers in reading comprehension, students were successful in identifying the structures and elements of the text types. By using the graphic organizers, the students were able to understand the reading concepts. In utilizing literacy strategies like graphic organizers, student learning and independence is increased and they are more prepared to practice these skills independently.